Storable and injectable root canal filling material and preparation method thereof

By using components such as magnesium phosphate and biphosphate in the root canal filling material, combining antibacterial and surfactant, reacting and curing only after encountering water, the problem of insufficient antibacterial and sealing properties of existing materials is solved, and the problem of insufficient antibacteriality and sealing properties of existing materials is achieved. Long-term storage and efficient sealing performance of materials.

CN116492230BActive Publication Date: 2024-12-20WUHAN UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310619117.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2023-05-25
Filing Date
2023-05-29
Publication Date
2024-12-20
Estimated Expiration
2043-05-29

AI Technical Summary

Technical Problem

The existing root canal filling materials have shortcomings in antibacterial, enclosure and biocompatibility, especially the problems of high solubility of bioceramic materials and poor long-term antibacterial performance.

Method used

Magnesium phosphate, biphosphate, antibacterial agent and developer are used as solid phase components, and combined with stabilizers, solubilizers and surfactants are used as liquid phase components, paste-like materials are prepared by particle grading method, only when exposed to water After the reaction is cured, the phosphoric acid composite brine is formed, which improves the sealing performance and fluidity.

Benefits of technology

It achieves long-term storage of materials and good antibacterial properties, has the ability to easily inject and seal the root canal, provides good cell compatibility and low solubility, while simplifying the preparation process and production process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116492230B_ABST
    Figure CN116492230B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of medical materials, and in particular to a storable and injectable root canal filling material and a preparation method thereof, comprising a solid phase component and a liquid phase component: the solid phase component comprises magnesium phosphate, hydrogen phosphate, an antibacterial agent and a developer. After the slurry of the material of the present invention encounters water, the solid phase component in the material begins to hydrate and harden, and can effectively seal the root canal and has a certain strength. The hydration product of the material is non-toxic, harmless and non-irritating. The material of the present invention has good injectability, can be easily squeezed out of the syringe without residue, can effectively seal the root canal after injection filling, the injection is completed once, and the injection force is small. In addition, the sealant can maintain fluidity for a long time and is easy to use. The material of the present invention can provide good antibacterial properties for a long time, has a good killing effect on Gram-positive bacteria that cause periodontal disease and pulpitis, has an inhibitory and destructive effect on bacterial biofilms, and can effectively prevent postoperative infection problems.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of medical materials, and in particular to a storable and injectable root canal filling material and a preparation method thereof. Background Art

[0002] Root canal filling is an effective method for treating oral diseases such as pulp disease and periapical disease. Root canal filling materials are a very critical factor in root canal treatment. The principle of root canal treatment is to control infection, and the ideal goal of root canal treatment is to remove all bacteria and seal all root canals. Therefore, perfect antibacterial properties, filling and sealing are the difficulties and key points of root canal treatment. Root canal filling materials are the key to solving the above difficulties. Filling materials have also been continuously developing in recent years. At present, the following root canal sealers are commonly used in clinical practice.

[0003] 1. Zinc oxide eugenol paste: This type of sealant has been used for a long time. The eugenol in its ingredients has antibacterial function and has different degrees of inhibition on most facultative bacteria and a few anaerobic bacteria. However, this type of root canal filling agent cannot achieve the inertness and no side effects required by the ideal sealant.

[0004] 2. Resin root canal sealers: Resin root canal sealers are widely used due to their good antibacterial effect, sealing ability and physical and chemical ability. According to their main ingredients, they can be divided into epoxy resin sealers and methacrylate sealers. The antibacterial effect of this type of sealer mainly comes from the bisphenol A-diglycidyl ether and formaldehyde components released during the curing process. For example, AH-plus, which is commonly used in the market, is this type of sealer. However, this type of sealer also has disadvantages such as cytotoxicity, strong stimulation after overfilling, and poor absorption.

[0005] 3. Calcium hydroxide sealant: Calcium hydroxide sealant is also a type of sealant that has been used for a long time. It mainly releases hydroxide ions during the curing process to increase the pH value in the surrounding environment, thereby exerting an antibacterial effect. However, due to the dissolution of calcium hydroxide, the sealant is greatly degraded and the sealing performance is insufficient.

[0006] 4. Bioceramic sealers: These are relatively more commonly used and researched sealers in recent years. They mainly use calcium silicate or calcium phosphate as the base material. They have good cell compatibility, biocompatibility, sealing and bonding properties, and also have certain antibacterial properties. In 2009, iRootSP (Innovative Bioceramix, Vancouver, Canada) was used clinically as the first root canal sealer in this category. iRootSP is a new type of bioceramic root canal sealer with calcium silicate as the base material. It is currently widely used in root canal treatment, root canal perforation repair, and apical barrier surgery. After that, many sealer-related studies and products used calcium silicate as the base material. This type of sealer is also the sealer with the best comprehensive performance. At present, its biggest problem is its high solubility and poor long-term antibacterial performance.

[0007] In addition, for bioceramic sealants, the particle size of the solid phase material used has a great influence on the performance of the sealant. For cement materials, the particle grading method is often used to improve the various properties of cement. Therefore, the particle grading method is also feasible for improving the performance of bioceramic sealants.

[0008] In summary, how to develop root canal filling agents with ideal antibacterial properties, sealing properties, physicochemical properties and biocompatibility remains a challenge. Summary of the invention

[0009] One of the purposes of the present invention is to provide a storable and injectable root canal filling material, which can be stored for a long time, is easy to use, and has good antibacterial properties and injectability.

[0010] The second object of the present invention is to provide a method for preparing a storable and injectable root canal filling material, which has a simple preparation process and is easy to adjust.

[0011] The solution adopted by the present invention to achieve one of the purposes is: a storable and injectable root canal filling material, including a solid phase component and a liquid phase component: the liquid-to-solid ratio of the solid phase component to the liquid phase component is 0.5-0.25mL:1g; the solid phase component includes magnesium phosphate, hydrogen phosphate, an antibacterial agent and a developer, and the percentages by mass are: magnesium phosphate accounts for 45%-70%, hydrogen phosphate accounts for 15%-25%, antibacterial agent accounts for 10%-30%, and developer accounts for 10%-30%; the liquid phase component includes a stabilizer, a solubilizer and a surfactant, and the percentages by mass are: the stabilizer accounts for 70%-90%, the solubilizer accounts for 10%-20%, and the surfactant accounts for 3%-8%.

[0012] The root canal filling material of the present invention is in the form of a paste and can be directly injected into the root canal through a syringe. After entering the root canal, it comes into contact with the moisture in the root canal to react and solidify. Reaction mechanism: the hydrogen phosphate in the component reacts with magnesium phosphate to produce a hydrate of a phosphate complex salt, which then hardens.

[0013] The root canal filling material of the present invention will react and solidify only when it encounters water, and will not react with the bioactive mixed oil. Therefore, the root canal filling material can be stored for a long time and maintain fluidity only if it does not come into contact with moisture and the oil does not volatilize, that is, it is stored in a sealed state at low temperature.

[0014] Preferably, in the magnesium phosphate, the component with a particle size of 2-5 μm accounts for 30%-70% of the total mass of the magnesium phosphate, and the component with a particle size of 10-25 μm accounts for 30%-70% of the total mass of the magnesium phosphate.

[0015] In the process of preparing the sealing agent, the present invention adopts a particle grading method to mix magnesium phosphates of different particle sizes in a certain proportion, thereby further enhancing the performance of the sealing agent.

[0016] Preferably, the hydrogen phosphate in the solid phase component is at least one of potassium dihydrogen phosphate, dipotassium hydrogen phosphate, sodium dihydrogen phosphate, and disodium hydrogen phosphate.

[0017] Preferably, the antibacterial agent in the solid phase component is at least one of magnesium oxide, zinc oxide and sodium oxide.

[0018] Preferably, the developer in the solid phase component is zirconium oxide or bismuth oxide.

[0019] Preferably, the surfactant in the liquid phase component is at least one of octadecyl phosphate, hexadecyl phosphate, tetradecyl phosphate, tridecyl phosphate and dodecyl phosphate.

[0020] Preferably, the solubilizer in the liquid phase component is castor oil polyoxyethylene ether, at least one of the castor oil polyoxyethylene ether EL-10, EL-20, EL-40, EL-80, and HEL-20.

[0021] Preferably, the stabilizer in the liquid phase component is caprylic / caprylic triglyceride.

[0022] The solution adopted by the present invention to achieve the second purpose is: a method for preparing the storable and injectable root canal filling material, the steps are as follows: after the liquid phase components are evenly mixed, they are evenly mixed with the solid phase components, and blended to form a slurry.

[0023] The present invention has the following advantages and beneficial effects:

[0024] 1. When the slurry of the material of the present invention encounters water, the solid phase components in the material begin to hydrate and harden, which can effectively seal the root canal and have a certain strength. The hydration product of the material is non-toxic, harmless and non-irritating.

[0025] 2. The material of the present invention has good injectability and can be easily squeezed out of the syringe with almost no residue. It can effectively seal the root canal after injection filling. The injection is completed in one time and the injection force is small. At the same time, the product itself is in paste form and has fluidity. It does not require on-site preparation and can be used immediately after being taken. It is easy to operate, which greatly reduces the operation time of medical staff and the consultation time of patients.

[0026] 3. The material of the present invention can provide good antibacterial properties for a long time, has a good killing effect on Gram-positive bacteria that cause periodontal disease and pulpitis, has an inhibitory and destructive effect on bacterial biofilms, and can effectively prevent post-operative infection problems.

[0027] 4. The material of the present invention is storable and can maintain good fluidity and injectability for a period of time when stored in a closed, water-free environment, making it easy to use.

[0028] 5. The material prepared by the present invention contains magnesium element, all proportions are non-toxic and harmless, and has good cell compatibility, good sealing property, and low solubility.

[0029] 6. The material preparation process provided by the present invention is simple, and there is no order requirement for adding the components, which facilitates mechanized and large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a graph showing the antibacterial test results of the root canal filling materials with different ratios prepared by the present invention against Enterococcus faecalis;

[0031] Figure 2 The CCK-8 test results of the root canal filling materials with different proportions prepared by the present invention;

[0032] Figure 3 This is a graph showing the injection force test results of root canal filling materials with different ratios prepared by the present invention;

[0033] Figure 4 This is a diagram showing the injection performance of the root canal filling materials with different ratios prepared by the present invention after extrusion test;

[0034] Figure 5 A scanned image of the tooth slice interface after the root canal filling material prepared by the present invention is filled into the tooth;

[0035] Figure 6 This is a graph showing the degradation results of the root canal filling material prepared by the present invention after being immersed in deionized water for 7 days;

[0036] Figure 7 This is a graph showing the fluidity test results of the root canal filling material prepared by the present invention;

[0037] Figure 8 The fluidity test results of the root canal filling materials of Examples 3-5 and Comparative Example 2 of the present invention are shown in FIG.

[0038] Fig. 9 The antibacterial test results of the root canal filling materials of Examples 3-5 of the present invention and Comparative Example 2 are shown;

[0039] Fig.10 This is a developing effect diagram of the root canal filling material prepared by the present invention;

[0040] Fig.11 This is a comparison result of the fluidity between the sealing agent after particle grading prepared by the present invention and the sealing agent without particle grading;

[0041] Fig.12 This is a comparison diagram of the solubility of the sealing agent after particle grading prepared by the present invention and the sealing agent without particle grading. DETAILED DESCRIPTION

[0042] For a better understanding of the present invention, the following examples are provided to further illustrate the present invention, but the present invention is not limited to the following examples.

[0043] Example 1

[0044] Weigh 9.6g magnesium phosphate (including 4.8g magnesium phosphate with a particle size of 2-5μm and 4.8g magnesium phosphate with a particle size of 10-25μm), 2.4g magnesium oxide, 3g potassium dihydrogen phosphate, and 3.75g zirconium oxide to form a mixture, and then weigh 5.05g caprylic / caprylic triglyceride (GTCC), 0.91g EL40, and 0.26g hexadecyl phosphate. Mix the above ingredients, mechanically ball-mill, and store in a syringe.

[0045] Example 2

[0046] Weigh 16 g of magnesium phosphate (including 8 g of magnesium phosphate with a particle size of 2-5 μm and 8 g of magnesium phosphate with a particle size of 10-25 μm), 4 g of magnesium oxide, 5 g of potassium dihydrogen phosphate, and 2.78 g of zirconium oxide to form a solid mixture, then weigh 7.5 g of GTCC, 1.36 g of EL20, and 0.4 g of tetradecyl phosphate, mix the above ingredients, ball-mill, and store them in a syringe for later use.

[0047] Example 3

[0048] Weigh 9.6g magnesium phosphate (including 4.8g magnesium phosphate with a particle size of 2-5μm and 4.8g magnesium phosphate with a particle size of 10-25μm), 2.4g zinc oxide, 3g sodium dihydrogen phosphate, and 3.75g bismuth oxide to form a mixture, and then weigh 5.05g caprylic / capric triglyceride (GTCC), 0.91g EL20, and 0.26g tetradecyl phosphate. Mix the above ingredients, mechanically ball-mill, and store in a syringe.

[0049] Example 4

[0050] Weigh 9.6g magnesium phosphate (including 4.8g magnesium phosphate with a particle size of 2-5μm and 4.8g magnesium phosphate with a particle size of 10-25μm), 2.4g magnesium oxide, 3g disodium hydrogen phosphate, 3.75g zirconium oxide to form a mixture, and then weigh 5.05g caprylic / capric triglyceride (GTCC), 0.91g EL40, and 0.26g octadecyl phosphate. Mix the above ingredients, mechanically ball-mill, and store in a syringe.

[0051] Example 5

[0052] Weigh 9.6g magnesium phosphate (including 4.8g magnesium phosphate with a particle size of 2-5μm and 4.8g magnesium phosphate with a particle size of 10-25μm), 2.4g zinc oxide, 3g dipotassium hydrogen phosphate, and 3.75g zirconium oxide to form a mixture, and then weigh 5.05g caprylic / capric triglyceride (GTCC), 0.91g EL80, and 0.26g octadecyl phosphate. Mix the above ingredients, mechanically ball-mill, and store in a syringe.

[0053] Example 6

[0054] Weigh 9.6g magnesium phosphate (including 2.88g magnesium phosphate with a particle size of 2-5μm and 6.72g magnesium phosphate with a particle size of 10-25μm), 2.4g magnesium oxide, 3g disodium hydrogen phosphate, and 3.75g zirconium oxide to form a mixture, and then weigh 5.05g caprylic / capric triglyceride (GTCC), 0.91g EL40, and 0.26g octadecyl phosphate. Mix the above ingredients, mechanically ball-mill, and store in a syringe.

[0055] Example 7

[0056] Weigh 9.6g magnesium phosphate (6.72g of magnesium phosphate with a particle size of 2-5μm and 2.88g of magnesium phosphate with a particle size of 10-25μm), 2.4g zinc oxide, 3g dipotassium hydrogen phosphate, and 3.75g zirconium oxide to form a mixture, and then weigh 5.05g caprylic / capric triglyceride (GTCC), 0.91g EL80, and 0.26g octadecyl phosphate. Mix the above ingredients, mechanically ball-mill, and store in a syringe.

[0057] The sealants prepared in Examples 1-7 were stored in syringes and placed in a closed, dry environment. Part of the sealants were squeezed out on the 7th, 14th, 21st, and 28th days, and their fluidity was tested according to the above method. The results are shown in Table 1. It can be seen that the fluidity of the sealants in all Examples did not change much within 28 days and all met the standard requirements (17 mm), indicating that the sealants are storable.

[0058] Table 1 Data on the change in fluidity of the sealants prepared in Examples 1-7 after continuous storage in a syringe for 28 days

[0059] 7 days 14 days 21 days 28 days Example 1 23.28mm 22.74mm 22.84mm 22.56mm Example 2 22.89mm 23.01mm 22.00mm 22.45mm Example 3 23.06mm 23.00mm 22.72mm 22.84mm Example 4 22.81mm 22.64mm 22.60mm 22.54mm Example 5 23.44mm 23.20mm 23.22mm 22.98mm Example 6 26.32mm 26.08mm 26.16mm 25.96mm Example 7 19.78mm 19.86mm 19.64mm 19.32mm

[0060] Comparative Example 1

[0061] Weigh 8g of magnesium phosphate (including 4g of magnesium phosphate with a particle size of 2-5μm and 4g of magnesium phosphate with a particle size of 10-25μm), 2g of zinc oxide, 2.5g of potassium dihydrogen phosphate, and 0.66g of zirconium oxide to form a solid phase mixture, and then weigh 3.55g of GTCC, 0.65g of EL40, and 0.19g of hexadecyl phosphate. Mix the above ingredients, mechanically ball mill, and store in a syringe. (Example of insufficient developer content)

[0062] Comparative Example 2

[0063] Weigh 8g of magnesium phosphate (including 4g of magnesium phosphate with a particle size of 2-5μm and 4g of magnesium phosphate with a particle size of 10-25μm) and 2g of potassium dihydrogen phosphate to form a solid phase mixture, and then weigh 2.7g of GTCC, 0.49g of EL40, and 0.14g of hexadecyl phosphate. Mix the above ingredients, mechanically ball-mill, and store them in a syringe.

[0064] Comparative Example 3

[0065] Weigh 8g of magnesium phosphate (including 4g of magnesium phosphate with a particle size of 2-5μm and 4g of magnesium phosphate with a particle size of 10-25μm), 2g of magnesium oxide, and 2.5g of potassium dihydrogen phosphate to form a solid phase mixture, and then weigh 3.38g of GTCC, 0.61g of EL40, and 0.18g of hexadecyl phosphate. Mix the above ingredients, mechanically ball-mill, and store in a syringe. (An example containing an antibacterial agent but not a developer).

[0066] Comparative Example 4

[0067] Weigh 9.6g magnesium phosphate (all with a particle size of 2-5μm), 2.4g magnesium oxide, 3g potassium dihydrogen phosphate, 3.75g zirconium oxide to form a mixture, and then weigh 5.05g caprylic / caprylic triglyceride (GTCC), 0.91g EL40, and 0.26g hexadecyl phosphate. Mix the above ingredients, mechanically ball mill, and store in a syringe. (Ungraded, the matrix materials are all small particles)

[0068] Comparative Example 5

[0069] Weigh 9.6g magnesium phosphate (all with a particle size of 10-25μm), 2.4g magnesium oxide, 3g potassium dihydrogen phosphate, 3.75g zirconium oxide to form a mixture, and then weigh 5.05g caprylic / caprylic triglyceride (GTCC), 0.91g EL40, and 0.26g hexadecyl phosphate. Mix the above ingredients, mechanically ball mill, and store in a syringe. (Ungraded, the matrix materials are all large particles)

[0070] The root canal filling materials prepared in Examples 1-2 and Comparative Examples 1-3 were subjected to antibacterial experiments against Enterococcus faecalis. First, various root canal filling materials were soaked in deionized water, solidified and dried, and then ground into powder. The solidified root canal filling material powder was then placed on a workbench and sterilized under ultraviolet light. 30 mg of each sample was placed in a 24-well plate, and then 0.9 mL of PBS solution and 0.1 mL of bacterial suspension were added to each well. One well was selected without adding a sample as a blank control group. The well plate was placed in a 37°C incubator and cultured for 24 hours. After the culture was completed, the bacterial suspension in each well was diluted to 1 / 10 using a sterile PBS solution. 6 After the dilution is completed, take out 100 μL of the diluted liquid and drop it on the BHI solid culture medium, then use a high-temperature sterilized triangular coating rod to evenly spread the droplets on the culture dish. Place the solid culture medium after smearing in a constant temperature incubator at 37°C for 1 day, then take it out and observe the number of colonies on the solid culture medium. The results are as follows Figure 1 As shown, it can be seen from the figure that many bacterial colonies grow on the culture medium of the blank control group and TMP, while there are only individual bacterial colonies on the culture medium of the three groups of root canal filling materials containing magnesium oxide, indicating that the root canal filling materials containing antibacterial agents have good antibacterial properties.

[0071] The root canal filling material prepared in Example 1-2 was used to test cell compatibility, and BMSCs were used as experimental cells. The Cell Counting Kit-8 (CCK8) kit was used to detect the effect of the root canal filling material on cell proliferation. 10% fetal bovine serum and 1% penicillin-streptomycin were added to the α-MEM medium to prepare a complete culture medium. The subsequent cell culture and extract preparation were all made with the prepared MEM culture medium. TMP, 10% ZrO2 / MgO / TMP and 20% ZrO2 / MgO / TMP that had been hydrated for 3 days were soaked in α-MEM culture medium at a ratio of 0.2 g / mL, shaken for 24 hours, and then the supernatant was collected through a filter membrane, and the supernatant was diluted 2 times with culture medium. The cells cultured in 4.3.3.1 were distributed into a 96-well plate, and 100 μL BMSCs suspension was added to each well. The cell density was 2×10 4 Cell / ml, after culturing in a CO2 incubator for 24 hours, the culture medium was removed, the diluted extract was added, and the culture was continued. The cytotoxicity was tested after 1 day and 3 days respectively. During the test, the extract was removed, 100 μl of the prepared CCK8 solution (diluted 10 times with culture medium) was added to each well, and then kept still and cultured in a CO2 incubator for 3 hours. After shaking thoroughly on an oscillator, the optical density of the solution in each well was measured by a microplate reader (wavelength 450nm). The optical density value is used to characterize the viability of the cells in the air of the well plate. The CCK-8 test results are as follows. Figure 2 As shown, it can be seen from the figure that at this concentration, there is no significant difference in the cell viability of all embodiments, and the cell viability increases with the number of days, indicating that the cells can proliferate and grow normally, indicating that the root canal filling material prepared by the present invention has good cell compatibility.

[0072] The root canal filling materials prepared in Examples 1-2 and Comparative Example 2 were subjected to an injection test. Specifically, the root canal filling materials were placed in a syringe, and the syringe piston was squeezed by a mechanical testing machine. The pressure received by the syringe during the squeezing process was tested by the mechanical testing machine. The results show that the root canal filling materials can be easily squeezed out of the syringe. The results are as follows: Figure 3 As shown in the figure, it can be seen that the injection force of all different components of root canal filling materials during the injection process does not exceed 10N, and the injection force will not increase until the injection is completed due to the squeezing of the syringe, indicating that the root canal filling material prepared by the present invention still has good injectability after adding contrast agent and antibacterial agent.

[0073] The root canal filling materials prepared in Examples 1-2 and Comparative Example 2 were subjected to the above extrusion test. The injection performance after extrusion is shown in the figure below. Figure 4 As shown, it can be seen from the figure that all the root canal filling materials can be completely squeezed out of the syringe, indicating that the root canal filling materials prepared by the present invention have good injectability.

[0074] Prepare the root canal filling material prepared in Example 1-2, select the teeth filled with the root canal filling material, and soak them in normal saline for 7 days. Use a resin curing agent to cure the filled teeth in the mold. When the curing agent is completely hardened, take out the embedded block, saw it into a square with a saw, and then use a water-cooled slicer (Leica SP 1600, Germany) to cut the embedded block in a direction horizontal to the root canal. Use a scanning electron microscope to observe the morphology of the cross-section of the filled teeth, focusing on the morphology of the interface between the dentin and the root canal filling material, and pay attention to whether there are obvious cracks or damaged areas. If not, it means that the root canal filling material and the dentin can be well bonded. The scanned image of the tooth slice interface is as follows: Figure 5 As shown, there is no obvious gap between the dentin and the root canal filling material, and it has good sealing performance.

[0075] After the root canal filling materials prepared in Examples 1-2 and Comparative Example 12 are configured, the configured root canal filling materials are added to a mold with a diameter of 5 mm and a thickness of 1 mm. Nylon thread is inserted into the unsolidified slurry, and the sample is placed in an incubator at 37°C and 100% relative humidity for 48 hours. Take out after drying, and use an electronic balance to test the mass. After repeating three times, calculate the average value as the initial mass (m0). Then, each sample is placed in a centrifuge tube containing 5 ml of deionized water and cultured. Use nylon thread to suspend the sample in water without contacting the tube wall. After 7 days, take out the sample, measure the mass again after it is completely dried, and take the average value as the final mass (m f ). The solubility calculation formula is: (m0-m f ) / m0×100%. The solubility of all samples is as follows Figure 6 As shown, it can be seen that the solubility of all root canal filling materials does not exceed 3% after immersion for 7 days. Lower solubility is more conducive to the sealing of the root canal system.

[0076] The root canal filling materials prepared in Example 1-2 and Comparative Example 1-2 are prepared, and the fluidity test method of the root canal filling materials refers to the international standard ISO 6876 / 2012. Prepare two square glass plates (40×40×5mm), each weighing about 20g. Squeeze 0.05ml of the prepared premixed root canal filling material into the center of one glass plate through a syringe, place another glass plate on top of the root canal filling material, and then place a 100g weight on top. After 10 minutes, remove the weight and measure the diameter of the flattened root canal filling material. Repeat the measurement 3 times for each sample, and take the average value as the fluidity of the root canal filling material. According to the standard, the fluidity of the root canal filling material should be higher than 17mm. The fluidity test results of all root canal filling materials are as follows. Figure 7As shown in the figure, the fluidity is higher than 17mm, which meets the requirements of ISO 6876 / 2012. Good fluidity can ensure that the root canal is completely filled.

[0077] The root canal filling materials prepared in Examples 3-5 and Comparative Example 2 were prepared. The fluidity test method of the root canal filling materials has been described above. The fluidity test results of all the root canal filling materials are as follows: Figure 8 As shown in the figure, the fluidity is higher than 17mm, which meets the requirements of ISO 6876 / 2012. Good fluidity can ensure that the root canal is completely filled.

[0078] The root canal filling materials prepared in Examples 3-5 and Comparative Example 2 were prepared, and the antibacterial effects of all samples were tested according to the bacterial experimental method used above. Fig. 9 As shown, it can be seen that the sealants of Examples 3-5 also have good antibacterial effects.

[0079] The root canal filling materials prepared in Examples 1-2 and Comparative Examples 1 and 3 were injected into a mold with a diameter of 10 mm and a height of 1 mm, and then soaked in deionized water for 72 hours, removed, and dried for later use. At the same time, for reference, the thickness of the aluminum sheet was used to characterize the development effect of the root canal filling material, and aluminum sheets of different thicknesses (0.5-8.0 mm) were prepared. An X-ray computed tomography scanner (TOSHIBA, Japan) was used to measure the radiographic transparency of the sample, which included a tooth filled with a root canal filling material, a root canal filling material sheet solidified in a mold, and aluminum sheets of different thicknesses (0.5-8.0 mm). The development effect of the root canal filling material is as follows Fig.10 As shown, it can be seen that the developing effects of Examples 1 and 2 are very good, while the developing effect of the comparative example is not good.

[0080] The root canal filling materials prepared in Example 1 and Comparative Examples 4-5 were prepared. The fluidity test method of the root canal filling materials has been described above. The fluidity test results of all the root canal filling materials are as follows: Fig.11 As shown, it can be seen that the comparative example of the raw material with small particle size has poor fluidity, while the other two groups of sealing agents containing large particles have better fluidity.

[0081] The root canal filling materials prepared in Example 1 and Comparative Examples 4-5 were prepared, and the solubility of the sealant was tested according to the method mentioned above. The solubility test results of all root canal filling materials are as follows: Fig.12 As shown, it can be seen that the solubility of the sealer configured using the particle grading process is much lower than that of the sealer configured without the particle grading method. The lower the solubility, the more conducive it is to the sealing of the root canal system. Therefore, the particle grading process can optimize the solubility performance of the sealer.

[0082] The above is only a preferred embodiment of the present invention, which certainly cannot be used to limit the scope of rights of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and changes can be made without departing from the principle of the present invention, and these improvements and changes are also regarded as the protection scope of the present invention.

Claims

1. A storable and injectable root canal filling material, characterized in that: It includes a solid phase component and a liquid phase component: the liquid-to-solid ratio of the solid phase component to the liquid phase component is 0.5-0.25 mL: 1 g; the solid phase component includes magnesium phosphate, hydrogen phosphate, an antibacterial agent and a developer, and the percentages by mass are as follows: magnesium phosphate accounts for 45%-70%, hydrogen phosphate accounts for 15%-25%, the antibacterial agent accounts for 10%-30%, and the developer accounts for 10%-30%; the liquid phase component includes a stabilizer, a solubilizer and a surfactant, and the percentages by mass are as follows: the stabilizer accounts for 70%-90%, the solubilizer accounts for 10%-20%, and the surfactant accounts for 3%-8%; in the magnesium phosphate, the component with a particle size of 2-5 μm accounts for 30%-70% of the total mass of the magnesium phosphate, and the component with a particle size of 10-25 μm accounts for 30%-70% of the total mass of the magnesium phosphate.

2. The storable and injectable root canal filling material according to claim 1, characterized in that: The hydrogen phosphate in the solid phase component is at least one of potassium dihydrogen phosphate, dipotassium hydrogen phosphate, sodium dihydrogen phosphate, and disodium hydrogen phosphate.

3. The storable and injectable root canal filling material according to claim 1, characterized in that: The antibacterial agent in the solid phase component is at least one of magnesium oxide, zinc oxide and sodium oxide.

4. The storable, injectable root canal filling material according to claim 1, characterized in that: The developer in the solid phase component is zirconium oxide or bismuth oxide.

5. The storable and injectable root canal filling material according to claim 1, characterized in that: The surfactant in the liquid phase component is at least one of octadecyl phosphate, hexadecyl phosphate, tetradecyl phosphate, tridecyl phosphate and dodecyl phosphate.

6. The storable, injectable root canal filling material according to claim 1, characterized in that: The solubilizing agent in the liquid phase component is castor oil polyoxyethylene ether, and the castor oil polyoxyethylene ether is at least one of EL-10, EL-20, EL-40, EL-80, and HEL-20.

7. The storable, injectable root canal filling material according to claim 1, characterized in that: The stabilizer in the liquid phase component is caprylic / capric triglyceride.

8. A method for preparing a storable and injectable root canal filling material according to any one of claims 1 to 7, characterized in that: The steps are as follows: after the liquid phase components are evenly mixed, they are evenly mixed with the solid phase components, and blended to form a slurry.